Pathology of colorectal polyps and cancer. Issue 1 (January 2023) - Bateman, Adrian C.
Abstract: Colorectal cancer (CRC) is one of the most common cancers worldwide. However, early detection and treatment can lead to very good clinical outcomes. This article highlights the pathology-related aspects of CRC that are most relevant to colorectal surgeons. This includes sections on epidemiology, aetiology, presentation, macroscopic and microscopic features, pathological staging, prognosis, precursor lesions and molecular pathways, follow-up and bowel cancer screening. The main section on CRC is preceded by a description of the types of colorectal polyp that are most commonly encountered in clinical practice, many of which are associated with the development of CRC.